WHEN WATER BECOMES A FRENEMY: A CASE SERIES ON THIRSTY CHILDREN AND LITERATURE REVIEW - Robert, Kelcina Mary; Ong, Jayne AX; Lim, Poi Giok (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Polydipsia is defined as excessive thirst causing the consumption of large amounts of fluids, more than 2 liters/m²/day in children, with consequential polyuria. It is of paramount importance to distinguish between diabetes insipidus (DI) and primary polydipsia as treatment differs, and inappropriate use of desmopressin can be detrimental in patients with primary polydipsia. CASE We present 3 children referred to the Paediatric Endocrine Clinic who exhibited a long history of excessive drinking. Case 1. A 9-year-old male presented with an unquenchable thirst, drinking 6 to 8 L per day that required him to wake up 3–4 times nightly to drink water. A water deprivation test was performed, yielding inconclusive results, hence needed further investigation. Case 2. A 9-year-old male's excessive drinking during school hours concerned his teachers, prompting an investigation. A subsequent water deprivation test confirmed primary polydipsia. Case 3. A 2-year-old toddler presented with a progressive history of excessive drinking. Although his water deprivation test showed equivocal findings, his cranial MRI confirmed the diagnosis of central DI. Fortunately, our patients did not demonstrate any red flags, such as dehydration, visual field loss, recurrent vomiting, headache or altered consciousness. Our school-going patients denied a history of school bullying or truancy. None of the children were on medication and there was no family history of similar symptoms. CONCLUSION These cases underscore the importance and limitations of a water deprivation test in diagnosing polydipsia and polyuria in children. Inconclusive results must be interpreted with caution and necessitate further investigation, as baseline clinical and biochemical variables cannot substitute for the water deprivation test.